Current indications for abdominal-based flaps in hand and forearm reconstruction. Issue 12 (December 2020) - Wagner, Ryan D.; Carr, Logan; Netscher, David T.
Highlights: The ultimate goal of upper extremity reconstruction is to restore function, retain sensation, and preserve mobility. Extensive soft tissue loss or injury of the hand and forearm is a challenging problem traditionally treated with abdominal-based flaps. Abdominal flap options include the groin flap, the Scarpa's fascia flap, and the paraumbilical perforator flap. While microsurgical reconstruction is now more routine, several indications for abdominal-based flaps remain valid. Indications include patient factors, absence of recipient vessels, need to preserve vessels for reconstruction, large multi-surface wounds. Abstract: Extensive soft tissue loss or injury of the hand and upper extremity is a challenging reconstructive problem traditionally treated with abdominal-based pedicled flaps. Options for coverage included the groin flap based on the superficial circumflex iliac artery, the Scarpa's fascia flap based on the superficial inferior epigastric artery, and the paraumbilical perforator flap from the deep inferior epigastric artery perforators. Despite the ability to provide consistent and pliable soft tissue coverage with ease of elevation, these flaps have several disadvantages including restriction of mobility, requirement for multiple procedures, bulkiness and patient discomfort. With the advent of microsurgery, pedicled regional flaps, and off-the-shelf skin substitutes, the applications for these flaps have narrowed. However several indications still remain. These include: patient and facility factors which deter microsurgery, the absence of recipient vessels after injury, prior surgical use of recipient vessels, the need to preserve major vessels for future reconstruction, and large multi-surface wounds requiring coverage. In this review we detail these indications and provide case examples for each.